Analisis Kepuasan Konsumen Terhadap Inovasi Batik dan Model Busana Monokrom Berbasis Zero-Waste Pada Brand De’youl - Sevi Dewi Pratiwi; Purwosiwi Pandansari (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study examines consumer satisfaction with zero-waste monochrome batik fashion innovation at the De'Youl Batik brand. The study is grounded in the limited discussion of consumer responses to zero-waste monochrome batik products; previous studies have generally emphasized design exploration, production techniques, or sustainability discourse. A descriptive mixed-method approach was used by combining qualitative data from interviews, observation, expert assessment, and producer assessment with simple quantitative data from a five-point Likert questionnaire. Twenty regular consumers aged 18-35 completed the questionnaire, while five VIP consumers were interviewed to obtain deeper information about product experience. Data validation was conducted through source triangulation involving consumers, producer/owner, and design experts. Quantitative data were converted into percentages, while qualitative data were analyzed thematically. The findings show a high level of satisfaction, with an average score of 91%. The strongest indicator was repurchase intention (4.70; 94%), followed by material comfort (4.65; 93%), trend and aesthetic suitability (4.50; 90%), and sewing/construction quality (4.35; 87%). Qualitative findings indicate that consumers perceive the product as modern, flexible, comfortable, exclusive, and aligned with sustainability values. This study contributes to the evaluation of sustainable local fashion by showing that zero-waste batik innovation can be commercially accepted when aesthetic, functional, and ethical values are integrated in the design process.